Post-pandemic one health: Unpacking the role of greenspaces and human-dog interactions in long-term health and well-being - Yi Peng; Yusong Ke; Rui Cai; Bingyang Lv; Shiliang Liu; Yuzhou Liu; Xi Li; Huixing Song; Qibing Chen (One Health)
The social isolation measures implemented during the outbreak of COVID-19 in 2020 have had lasting effects on public health and well-being. In response, a growing body of discourse has emerged to examine the long-term impacts of the pandemic on human health and welfare. Addressing these complex challenges requires innovative, interdisciplinary approaches grounded in a conceptual framework that integrates perspectives from both the social and natural sciences.At the intersection of human-animal-green space interactions, the One Health framework has become a prominent driver of holistic health research. However, there is still a lack of comprehensive reviews on how this framework has been applied to investigate the interconnected health and well-being outcomes associated with these dynamics. To fill this gap, the present study conducted a systematic scoping review to identify patterns, gaps, and key themes in the literature, while outlining priorities and considerations for future research.Following standardized PRISMA guidelines, the review employed clearly defined inclusion and exclusion criteria, along with dual-reviewer screening and data extraction procedures. A total of 29 studies were included, all of which directly or indirectly utilized the One Health framework. These studies were categorized into two primary thematic areas: (1) the role of green spaces in promoting human health in the post-pandemic context, and (2) emotional interactions between humans and animals during the pandemic. A notable trend in the literature is the incorporation of the Sense of Coherence as a key dimension of health and well-being within the One Health framework, highlighting the potential of human-dog-green space interactions to contribute meaningfully to salutogenic health processes.The limited number of studies identified also reflects the current underrepresentation of well-being as a core pillar within established One Health research. Based on existing evidence, this review provides a foundational reference for researchers seeking to explore health and well-being through a One Health perspective. It offers guidance for future investigations into the synergistic effects of human-dog-green space interactions on well-being, and proposes data-driven interventions and policy recommendations to address both general health outcomes and the prolonged effects of COVID-19.